The Relationship of Self Monitoring with Learning Outcomes (Study On Class X Vocational School Students Muhammadiyah 1 Padang) - Nada, Afifa Qatrun (Jurnal Riset Ilmu Pendidikan, 2022)
This research is motivated by the existence of students who do not do assignments during the learning process, students who have less than optimal learning outcomes who get scores below the KKM. This study aims to determine: 1) Self-monitoring of students in class X SMK Muhammadiyah 1 Padang. 2) The learning outcomes of students in class X SMK Muhammadiyah 1 Padang. 3) Self-monitoring with the learning outcomes of class X students of SMK Muhammadiyah 1 Padang. This type of research is descriptive quantitative with a correlational approach. The population of this study were students of class X TKJ, X TBSM 2, and class X TITL, totaling 53 students. The sampling technique was carried out by the total sampling technique, namely as many as 53 students who became the research sample. The results of this study indicate: 1) Self-Monitoring of class X students of SMK Muhammadiyah 1 Padang is in the good category. 2) The learning outcomes of Class X students of SMK Muhammadiyah 1 Padang are in the fairly good category. 3) There is a relationship between Self-Monitoring and the learning outcomes of Class X students of SMK Muhammadiyah 1 Padang with a fairly strong cohesiveness with a correlation value of 0.475. For this reason, it is recommended for BK teachers and subject teachers to provide services and motivation in order to improve the Self-Monitoring of students from good to very good categories and it is recommended to BK teachers and subject teachers to be able to motivate students in improving student learning outcomes. into the very good category.